2017
DOI: 10.1111/ruso.12180
|View full text |Cite
|
Sign up to set email alerts
|

Food Self‐provisioning in Europe: An Exploration of Sociodemographic Factors in Five Regions

Abstract: This article presents the results of an international comparative study on food self‐provisioning, an activity still widespread in the countries of the Global North. We collected the data in a sociological survey done in 2010 as a part of the household energy use research project GILDED. We selected a region with urban and rural areas as a case study in each of the five EU countries, including Scotland, the Netherlands, Germany, the Czech Republic, and Hungary. Our article raises two main research questions: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 40 publications
(137 reference statements)
0
32
0
Order By: Relevance
“…As such, our research complements large-scale quantitative studies on gardening populations in different European countries [52,53] and invites future comparative studies. To our knowledge, comparisons of gardening practices in CEE and Western Europe are rare, as scholarship on both regions comprises largely separate literatures.…”
Section: Discussionmentioning
confidence: 70%
“…As such, our research complements large-scale quantitative studies on gardening populations in different European countries [52,53] and invites future comparative studies. To our knowledge, comparisons of gardening practices in CEE and Western Europe are rare, as scholarship on both regions comprises largely separate literatures.…”
Section: Discussionmentioning
confidence: 70%
“…Except for a growing interest in the more general issue of vague urban terrains and urban wilderness (for example, Zemková, 2012; Haluzík, forthcoming), a bourgeoning issue in relation to urban gardening is alternative food production (Smith and Jehlička, 2007;Jehlička and Smith, 2011;Jehlička et al, 2013;Sovová, 2015;Vávra et al, 2018) and more recently also urban agriculture in general (Tóth et al, 2014;Duží et al, 2017). Except for a growing interest in the more general issue of vague urban terrains and urban wilderness (for example, Zemková, 2012; Haluzík, forthcoming), a bourgeoning issue in relation to urban gardening is alternative food production (Smith and Jehlička, 2007;Jehlička and Smith, 2011;Jehlička et al, 2013;Sovová, 2015;Vávra et al, 2018) and more recently also urban agriculture in general (Tóth et al, 2014;Duží et al, 2017).…”
Section: Theoretical Situating Of the Explorations Of Prague Allotmentsmentioning
confidence: 99%
“…In the particular context of the Czech Republic, studies exploring the cultural and historical specificity of urban nature together with its political-ecological aspects, especially with emphasis on urban gardening, are scarce. Except for a growing interest in the more general issue of vague urban terrains and urban wilderness (for example, Zemková, 2012; Haluzík, forthcoming), a bourgeoning issue in relation to urban gardening is alternative food production (Smith and Jehlička, 2007;Jehlička and Smith, 2011;Jehlička et al, 2013;Sovová, 2015;Vávra et al, 2018) and more recently also urban agriculture in general (Tóth et al, 2014;Duží et al, 2017). Studies of allotments in particular have focused on contemporary experience and practices of urban gardening (Gibas et al, 2014;Gibas et al, forthcoming) as well as on historical developments and related negotiations over allotments (Gibas et al, 2010;Pauknerová and Gibas, 2011;Spilková and Vágner, 2016;Tóth et al, 2018).…”
Section: Theoretical Situating Of the Explorations Of Prague Allotmentsmentioning
confidence: 99%
“…Studies aiming to estimate this domestic production are scarce, but they all confirm the persistence of an ancient phenomenon that is still firmly rooted in the food landscape of the cities of the globalised North (studies cited in [13]): In North America, a national study estimated that 25% of resident households in the United States self-produced part of their food [21], while more targeted studies of large cities in the USA [22,23] and Canada [24,25] showed that between 40% and 50% of households surveyed grew a vegetable garden. In Europe, a quantitative questionnaire survey that includes five regions from five countries compared in each case the answers of urban and rural respondents and estimated that the share of urban households engaged in food gardening activities in urban areas varies from 13% (Netherlands) to 49% (Hungary) and also showed that this self-production was strongly correlated with the ownership of a single-family house [26]. In France, a 2008 national survey on household food consumption revealed that nearly 30% of households living in suburban areas, where the single-family house dominates the urban landscape, declared that they self-produced part of their food [27].…”
Section: Introductionmentioning
confidence: 99%